Autoantibodies Against the Purkinje Cell Protein RGS8 in Paraneoplastic Cerebellar Syndrome. Issue 3 (May 2021) - Miske, Ramona; Scharf, Madeleine; Stark, Patrick; Dietzel, Heiko; Bien, Corinna I.; Borchers, Christian; Kermer, Pawel; Ott, Anthonina; Denno, Yvonne; Rochow, Nadine; Borowski, Kathrin; Finke, Carsten; et al.
Abstract : Objective: To describe the identification of regulator of G-protein signaling 8 (RGS8) as an autoantibody target in patients with cerebellar syndrome associated with lymphoma. Methods: Sera of 4 patients with a very similar unclassified reactivity against cerebellar Purkinje cells were used in antigen identification experiments. Immunoprecipitations with cerebellar lysates followed by mass spectrometry identified the autoantigen, which was verified by recombinant immunofluorescence assay, immunoblot, and ELISA with the recombinant protein. Results: The sera and CSF of 4 patients stained the Purkinje cells and molecular layer of the cerebellum. RGS8 was identified as the target antigen in all 4 sera. In a neutralization experiment, recombinant human RGS8 was able to neutralize the autoantibodies' tissue reaction. Patient sera and CSF showed a specific reactivity against recombinant RGS8 in ELISA and immunoblot, whereas no such reactivity was detectable in the controls. Clinical data were available for 2 of the 4 patients, remarkably both presented with cerebellar syndrome accompanied by B-cell lymphoma of the stomach (patient 1, 53 years) or Hodgkin lymphoma (patient 2, 74 years). Conclusion: Our results indicate that autoantibodies against the intracellular Purkinje cell protein RGS8 represent new markers for paraneoplastic cerebellar syndrome associated with lymphoma. Classification of Evidence: This study provided Class IV evidence that autoantibodies against the intracellular Purkinje cell protein RGS8 are associated with paraneoplastic cerebellar syndrome in lymphoma.